PENGARUH BIAYA TETAP DAN BIAYA VARIABEL TERHADAP PROFITABILITAS PT. PECEL LELE LELA INTERNASIONAL, CABANG 17, TANJUNG BARAT, JAKARTA SELATAN - Arief Rachmawan Assegaf (Jurnal Ekonomi dan Industri, 2019)
Effect of changes in interest Fixed Cost and Variable Cost to Probability of PT. Pecel Lele Lela International, Branch 17, Tanjung Barat, South Jakarta. The purpose of this research is to know is there any influence between in Fixed Cost and Variable Cost to Probability of PT. Pecel Lele Lela International, Branch 17, Tanjung Barat, south Jakarta Data resources in this research are changes of the income statement between 2009-2014, changes of financial position statement or balance between 2009-2014, The result of this research show a significant influence between the fixed cost and Variable Cost to Propability of PT. Pecel Lele Lela International, Branch 17, Tanjung Barat, South Jakarta. Based on result, there is a significant negative influence between fixed cost and variable cost to propability, In partial there is a significant negative influence between in fixed cost and variable cost to propability and The result of the changes in interest expense bank, exchange rate changes and changes in import quota are together significantly influence to probalilty